Unjust Enrichment from Official Corruption in Africa: Theory and Model on how Lenders have benefited - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
A 2015 World Bank report on the achievement of Millennium Development Goals (MDGs) revealed that since the 1990s, extreme poverty has been decreasing in all regions of the world with the exception of Africa where about 50 percent of countries in Sub-Saharan Africa did not achieve the MDG extreme poverty target despite the sub-region enjoying more than two decades of GDP growth resurgence. The purpose of this chapter is twofold. First to understand the interconnections between the large pool of capital transferred to the OECD countries and the corrupt deposits of stolen public funds. Second, to illustrate how such diversion of funds overseas are related to the spread of poverty in the African economies. We enunciate a `poverty multiplier theory' and propose a model for its application within an African context. The `poverty multiplier theory' postulates that: (i) one unit of currency deposited abroad represents a loss in financial development at home (ii) a fraction of the unit currency placed in foreign bank accounts is redirected to the domestic economy in the form of external debt. This external debt is further siphoned overseas through interest and loan principal repayment. Policy implications of these processes are discussed.
Keywords: B20; F35; F50; O19; O55; 330; Poverty; External Debts; Corruption; Capital flight; Development